PENERAPAN MODEL PEMBELAJARAN TTW (THINK-TALK-WRITE) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Elisa Gustina; Laili Habibah Pasaribu; Lily Rohanita Hasibuan (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The aim of this research is to determine the success of implementing the TTW (Think Talk Write) learning model in improving students' critical thinking skills. The type of research used is quantitative research with the method used in this research being quasi-experiment. The research results showed that the average post-test score was 69.50 with a standard deviation of 16.314 which was carried out in the experimental class using the TTW model. Meanwhile, the comparison class that used traditional learning methods obtained an average post-test score of 68.94 with a standard deviation of 17.386. So it can be concluded that classes that use the TTW (Think-Talk-Write) model have an effect on the critical thinking skills of class VIII students at Al-Washliyah Simpang Marbau Private MTS compared to students who do not use the TTW (Think-Talk-Write) model but use a learning approach traditional methods show less than optimal results in learning mathematics.